Detecting acute bilirubin encephalopathy in neonates based on multimodal MRI images and non-image clinical data - Miao Wu; Qian Liu; Can Lai (BMC Pediatrics)
Abstract Purpose Accurately detecting Acute bilirubin encephalopathy (ABE) from non-ABE neonates with hyperbilirubinemia (HB) condition remains a challenge in clinical practice. In this study, an automatic ABE diagnosing system based on multi-modal MRI images and non-image clinical metadata is proposed to address the issue. Methods A total of 75 ABE neonates and 75 non-ABE neonates with HB are included in the study. Each patient has 3 multi-modal magnetic resonance images and 8 non-image clinical features. To investigate the diagnosing model’s performance, 3 different feature sets, namely deep features from multi-modal MRI images, non-image clinical features, and fusion features, are extracted, respectively, and then further classified by a support vector machine (SVM), respectively. Results The results indicated the SVM classifier built on the fusion features achieved the best classification performance with an accuracy of 93.24 ± 2.35, specificity of 91.38 ± 4.45%, sensitivity of 95.11 ± 2.97%, precision of 91.87 ± 3.88%, area-under-the-curve (AUC) of 98.08 ± 1.16%, F1_score of 93.38 ± 2.23%. The performance of the SVM classifier built on the deep features was better than that built on the non-image clinical features. Conclusion Our study demonstrated that ABE diagnostic performance based on deep features from multi-modal MRI images could be significantly improved by incorporating clinical features. The proposed strategy may potentially be applicable to clinical practice to facilitate clinical management.